Perbandingan ekuitas merek indomie dan mie sedaap - Darmawan Darmawan; Syarifah Hudayah; Asnawati Asnawati (Faculty of Economics and Business Mulawarman University, 2016)
This study aimed to analyze the Comparative Effects of Brand Equity between Indomie Noodles brand and Sedaap noodles by using t test analysis in Two independent variables. The sample in this study were students of Mulawarman university Samarinda with amount of samples are 80 respondents by using hair method. The hypothesis of this study showed that between equity Indomie and Sedaap have significant differences. The results of hypothes test in Two Variables t test showed that, brand equity of Indomie and Mie Sedaap have significant differences.Keyword: Comparison of brand equity